PKM diversifikasi olahan rumput laut bagi perempuan Desa Lasitae Kabupaten Barru - Ratmawati Ratmawati; Ernawati S Kaseng; Ratnawati Fadillah (Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
Seaweed Farmer Group, technically not maximally managed seaweed business properly due to lack of knowledge andskills of PKM partner groups in processing seaweed so that it can be of economic value. It is expected that this CommunityPartnership Program, can solve the problems faced by partners through culinary products with better quantity and quality, bydiversifying processed seaweed products. This PKM approach: Participatory Learning and Action Community Empowerment.Using methods, namely: 1) lectures, 2) discussion and question and answer, and 3) demonstration and application. Thenaccompanied by assistance with the production process and the packaging process. PKM program results show 1) an increase inPKM partner knowledge about the benefits and nutritional value contained in seaweed, as well as how to diversify variousprocessed fresh seaweed; 2) PKM partners have skills in how to make seaweed meatballs and seaweed nuggets; 3) PKM partnershave the knowledge and skills on how to package good and healthy products, and label products so that they have economicalvalue.